"Extension's Partnership with the Future"; "To Educate a People"; "The Extension Organization of the Future"; Prairie Schooner Nebraska: The Individual Voice. - Jim Shaner; Jim King (Journal of Applied Communications, 1987)
Reviews of "Extension's Partnership with the Future," by Michael Quinn Patton; "To Educate a People"; "The Extension Organization of the Future"; Prairie Schooner Nebraska: The Individual Voice.